Examining How "Technology Show-off" Affects the Acceptance of Innovations in the Battery Electric Vehicle Sector. - Lampo, Alessandro (Association for Computing Machinery, 2024)
Theories and models try to describe the complexity of how people embrace and make use of innovations. The determinants of behavior concerning battery electric vehicles (BEVs) have traditionally revolved around factors such as vehicles’ price and range. Surprisingly, despite being small and one of the wealthiest territories in the world, Macau SAR faces challenges in BEV market penetration, underscoring the need to explore alternative causes of behavioral intention. To explain the adoption of technologies, this paper focuses on technology show-off (TS), which combines Rogers’ (2003) concepts of visibility and trialability of technology in a single construct as a determinant of behavioral intention. Therefore, when individuals perceive technology as more visible and available for trial, their behavioral intention to adopt it strengthens. Using structural equation modeling for quantitative analysis, this study examines the significance of TS in terms of the intention to adopt battery electric vehicles. The findings highlight the salience of the technology show-off construct in explaining behavioral intention, underscoring its significance in the context of modern society’s characteristics. This study contributes to advances in understanding technology acceptance and highlights the importance of incorporating experiential aspects (such as TS) into the traditional technology acceptance models.

Adapting the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) to the Acceptance of Public Policies - Lampo, Alessandro; Diakite, Ansoumane Douty; Ip, Emil Chi Hang (18th INTERNATIONAL CONFERENCE OF THE AGBRP - Leading Sustainability Transitions: Risk, Collaboration, and Technology, 2024)
The understanding of how people accept and embrace new policies is vital in today's world. This paper introduces an original way of looking at this by adapting the widely recognized Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2). The goal is to provide a foundational model for assessing policy acceptance. More specifically, we adapted the UTAUT-2 framework to study how Macau residents perceive the "Northbound Travel for Macau Vehicles" policy, which allows cars with Macau registration plates to enter China. Using structural equation modeling software (SmartPLS), we analyze data collected from 136 respondents who experienced the policy.Our findings reveal that Performance Expectancy (PE) and Habit (HB) significantly influence individuals' intention to take advantage of the policy. In other words, people are more likely to embrace policies they perceive as beneficial and that align with their existing habits. Effort Expectancy (EE) and Facilitating Conditions (FC) do not significantly impact acceptance, perhaps as a result of participants' familiarity with the policy and their resource availability. Surprisingly, while not directly tied to usage, Social Influence (SI) shows a high mean value, suggesting its potential role in policy acceptance when influential individuals adopt the policy. This pioneering research contributes to the field by bridging the gap between technology acceptance models and policy studies. Most importantly, it validates the use of the UTAUT-2 as a technology framework that is adapted for assessing policy acceptance.

The Moderating Effect of Food Neophilia on Consumers’ Intention to Use Insects as Food - Lampo, Alessandro; Sun, Hou Tong (18th INTERNATIONAL CONFERENCE OF THE AGBRP - Leading Sustainability Transitions: Risk, Collaboration, and Technology, 2024)
In a world where sustainable food choices are becoming increasingly important, this study explores the connection between food neophilia — the desire to experiment with new foods — and people's willingness to include insects in their diets. Using the Theory of Planned Behavior (TPB), our research delves into how neophilia (NP) moderates respondents’ attitude (ATT), social norms (SN), and perceived behavioral control (PBC) concerning the adoption of insects as a food source. The analysis draws from 160 self-administered surveys and employs structural equation modeling. Conducted in the context of Macau SAR (China), our study reveals the pivotal role that neophilia plays in shaping consumer attitudes and intentions. Notably, respondents generally expressed a willingness to explore novel culinary experiences. A positive moderating effect of neophilia on attitudes toward insect consumption is observed, suggesting that individuals with higher neophilia scores are more inclined to hold favorable intentions regarding insects as food. However, neophilia's influence on moderating SN and PBC exhibits contrasting effects, implying that a strong inclination for food neophilia may not necessarily leadto increased social pressure or perceived control in adopting insect-based diets. In light of these findings, this study recommends that practitioners and policymakers promote insect consumptionas an innovative and adventurous means of achieving sustainable nutrition. While the primary focus is on the impact of food neophilia on people's intention to consume insects as food, the study underscores the urgent need for diversified and sustainable dietary choices to address escalating environmental concerns and secure a resilient food supply for future generations.

Impact of Education on Green Fintech Adoption in a Smart City: Evidence from the Newly Developed Sub-city Center of Beijing. - Lei, Weng Chi; An, Boyang (18th INTERNATIONAL CONFERENCE OF THE AGBRP - Leading Sustainability Transitions: Risk, Collaboration, and Technology, 2024)
Integrating financial technologies with green initiatives is critical to the sustainable development agenda. This is particularly true for newly developed smart cities like Tongzhou, the sub-city center of Beijing. To assess the adoption of green fintech in Tongzhou, this paper extends the EnergyAugmented Technology Acceptance Model (EA-TAM) to incorporate two green factors – environmental awareness and green knowledge. This paper applies structural equation modeling techniques to analyze data from 403 respondents who live, work, or study in Tongzhou and finds allhypothesized constructs significant. Since green knowledge is significant to the adoption of green fintech, this paper further divides the sample into a high-education group (162 respondents with university-or-above degrees) and a low-education group (251 respondents with post-secondary-orlower degrees) to evaluate the impact of education. All the hypothesized factors are significant to the high-education group,but environmental awareness and perceived usefulness are insignificant to the low- education group. Hence, the results provide evidence that people in the newly developed smart city adopt green fintech due to their environmental sensitivity. The adoption of green fintech is more environmentally sensitive for people with high education levels.

The Role of the Country-of-Origin Effect in Driving Chinese EV Adoption: The Case of Portugal - Xian, Sitong; Lampo, Alessandro (18th INTERNATIONAL CONFERENCE OF THE AGBRP - Leading Sustainability Transitions: Risk, Collaboration, and Technology, 2024)
As environmental awareness grows, sustainable modes of transportation have garnered increasing importance. With the rising popularity of electric vehicles (EVs), a broader community now acknowledges their numerous advantages, such as lower noise levels, enhanced efficiency, and cost-effectiveness in comparison to traditional internal combustion engine vehicles. Furthermore, EVs significantly contribute to a more sustainable future by emitting fewer pollutants and reducing overall environmental impact. However, consumers' perceptions and expectations about the vehicle's country of origin - the nation where the vehicle is manufactured - remain unclear, particularly in the case of Chinese-manufactured EVs due to China's reputation for pollution and product safety concerns. This study employsa qualitative framework based on the Unified Theory of Acceptance and Use of Technology 2(UTAUT-2) to assess the acceptance of Chinese electric vehicles, and the influence of the Country-of-Origin Effect (COE) on a sample of Portuguese residents. Data was gathered through semi-structured interviews and analyzed using qualitative methods. The study's results shed light on the significance of the country of origin in shaping consumers' behavioral intentions to purchase Chinese electric vehicles, indicating a positive influence. This suggests that country of origin is a crucial factor when considering an individual's intention to adopt electric vehicles. Additionally, the research highlights the importance of various other factors such as performance expectancy, effort expectancy, social influence, facilitating conditions, price value, hedonic motivation, and habit in shaping consumers' attitudes and intentions. Our results underscore the complexity of consumer behavior toward electric vehicles, suggesting the need for a multifaceted approach to understanding andpromoting EV adoption. Research is needed to examine the COE in different cultural and geographic contexts to develop effective strategies to enhance the global adoption of electric vehicles, particularly from countries with varying environmental reputations

The Role of Habit in UTAUT-2 Research: A Study of BEV Users - Lampo, Alessandro (Association for Computing Machinery, 2023)
The UTAUT-2 offers the most comprehensive assessment of individual acceptance and use of technology to date. In particular, the theoretical additions of “hedonic motivation”, “price value”, and “habit”, made the model suitable for studying technology in a consumer context. However, a review of the literature revealed that the construct of habit has been dropped from a large number of studies. There are several reasons for this, including that the technologies examined were relatively new for the respondents to form a routine behavior. Therefore, this study aims to explore whether the construct can be used as a key predictor of future intention to use an innovation rather than an acquired practice among technology users. For this purpose, a conceptual model based on the theoretical additions to the UTAUT-2 is proposed and analyzed with structural equation modeling (SmartPLS). Our results showed significant relationships between the predictors and the behavioral intention to use battery electric vehicles (BEV) technology, and, in particular, depicted the construct of habit as the strongest factor in the decision to adopt the technology. In light of our findings, the construct of habit (HT) should be used in research together with the other UTAUT-2 predictors to assess individuals’ perceptions of possible future habitual behaviors.
Keywords: Battery Electric Vehicles (BEVs); Consumer Behavior; Habit; Process Innovation; Technology Acceptance; UTAUT-2.

Factors influencing disability inclusion practice on social media - Chan, Joye Wai Peng; Phillips, Jenny O.L. (Association for Computing Machinery, 2023)
Digital inclusion in Macao is in the very beginning stage, and disability inclusion practice on social media in producing and promoting accessible social media content and needs is hard to find. This study aims to analyse the factors that influence communication staff's practice of disability inclusion on social media by using the combined employee behaviour and communication process model to provide suggestions to management who wants to promote disability inclusion practice on social media.The Service Centre for the Deaf of the Macau Deaf Association (MDA) was selected as the object for this case study. The online social media used for MDA's communication was analysed, and semi-structured in-depth interviews with members of the Association were conducted. The research findings showed that, except for the reward structure, factors examined from the work environment in terms of organisation, supervision and co-workers; communication staff themselves; outcomes of accessible social media communication; audience and feedbacks show relations with disability inclusion practices on social media. The delivery of inclusive culture, the influential power of disability stakeholders and the positioning of social media platforms are the key influencing factors.The interesting part of this study is that people without disabilities seem to be excluded from the disability inclusion practice carried out on MDA's Facebook. Their social media content is highly accessible to deaf and hard-of-hearing audiences yet seems not to involve the general public. The study object is a good model for producing accessible content, yet the optimisation of promoting social media accessibility needs further exploration.
Keywords: Accessible Social Media (ASM); Disability Employment; Disability Inclusion; Macau Deaf Association

A Review on Open Innovation and Absorptive Capacity in Small and Medium Enterprises during the last decade - Analyzing Bibliometrics to Understand the Development of the Field - Ip, Chi Hang; Lobo Marques, Joao Alexandre; Dos Santos Silva, Bruno Riccelli; Cortez, Paulo Cesar; Barbosa, Alvaro (Association for Computing Machinery, 2023)
Small and medium-sized enterprises (SMEs) can benefit significantly from open innovation by gaining access to a broader range of resources and expertise using absorptive capacitive, and increasing their visibility and reputation. Nevertheless, multiple barriers impact their capacity to absorb new technologies or adapt to develop them. This paper aims to perform an analysis of relevant topics and trends in Open Innovation (OI) and Absorptive Capacity (AC) in SMEs based on a bibliometric review identifying relevant authors and countries, and highlighting significant research themes and trends. The defined string query is submitted to the Web of Science database, and the bibliometric analysis using VOSviewer software. The results indicate that the number of scientific publications has consistently increased during the past decade, indicating a growing interest of the scientific community, reflecting the industry interest and possibly adoption of OI, considering Absorptive. This bibliometric analysis can provide insights on the most relevant regions the research areas are under intensive development.
Keywords: Absorptive Capacity; Bibliometric analysis; Open innovation; SMEs; VOSviewer

Environmental Concern and the Intention to Use Eco-friendly Technologies: An Analysis of Battery Electric Vehicles in Macau. - Lampo, Alessandro; Silva, Susana C. (Association for Computing Machinery, 2023)
A growing number of people are becoming aware of the environmental footprint that our actions have on the environment. Research indicates that a key factor leading to the adoption of an electric vehicle is consumers’ high environmental concern. Indeed, the environmental concern (EC) construct is commonly associated with the purchase of sustainable and eco-friendly products in literature. Our study challenges this assumption. We examined how the environmental factor influenced the behavioral intention of Macau residents to adopt battery-electric vehicle (BEV) technology. For this purpose, we conducted a study based on the UTAUT-2 framework and used structural equation modeling (SmartPLS) to analyze the data. As a result, the choice of vehicles did not depend on the consumers’ level of concern. It appeared that consumers strongly perceived the benefits of a cleaner environment, however, when it comes to technology, environmental benefits are nice to have, rather than the primary incentive to purchase BEVs. Researchers should consider the role of environmental concern as a background factor in technology acceptance models, rather than a direct predictor of behavior. It is also recommended that marketers correctly consider this element when developing their product communications strategies, to appeal to the desired segment of customers.
Keywords: BEV; Clean Energy Technology; Environmental Footprint; Macau.; Sustainable Transportation; Technology Acceptance

An Exploratory Comparison of Stock Prices Prediction using Multiple Machine Learning Approaches based on Hong Kong Share Market - Lin, Chinyang; Lobo Marques, João Alexandre (Association for Computing Machinery, 2023)
Stock price prediction has always been challenging due to its volatility and unpredictability. This paper performs a preliminary exploratory comparison that utilizes Long Short-Term Memory (LSTM) and Support Vector Machine (SVM) algorithms to forecast the stock market in Hong Kong. It considers a public dataset publicly available and uses feature engineering to extract relevant features. Then, LSTM and SVM algorithms are applied to predict stock prices. Our results show that the proposed machine learning techniques can predict stock prices in Hong Kong's share market with the error metrics presented, and, for this purpose, LSTM achieved better results than SVM, with MSE = 0.0026, RMSE = 0.0508, MAE = 0.0406, and MAPE = 1.325.
Keywords: Long Short-Term Memory (LSTM); Machine Learning; Stock price prediction; Support Vector Machine (SVM); Time-series analysis

Facial expression for marketing and consumer behavior: A Bibliometric analysis from 2013-2023 using Data Visualization Tools - Qian, Cheng; Lobo Marques, Joao Alexandre (Association for Computing Machinery, 2023)
The classification of emotions based on facial expressions have been a new topic of research in recent years, especially in marketing and consumer behavior areas. However, there is lack of studies to understand how the research topic is developed in terms of bibliometric data. Therefore, the purpose of this work is to provide a bibliometric analysis of the research on the analysis of facial expressions for marketing and consumer behavior, identifying the state of the art, the latest research direction, and other indicators. We extracted data from Web of Science (WOS) platform, considering its core database, resulting in a total of 117 articles. The software Vosviewer was used to analyze the data and graphically visualize the results. This study indicates some of the most influential authors citations and coupling analysis in this specific field, identifies journals with the most published articles, and provide trends of the research area based on the analysis of keywords and corresponding number of articles per year. The results shows that 11 articles (9.4%) were cited more than 100 times, and the two most prolific authors published 5 articles, and the two most influential authors are Bouaziz Sofien and Pauly mark(270 citations) in this field. Of the 117 articles retrieved by WOS, more than 70% were published in high impact journals. The bibliometric analysis of the existing work in this study provides a valuable and reliable reference for researchers in this field and makes a reasonable prediction of the research direction trends.
Keywords: Bibliometric analysis; Consumer; Facial expression; Marketing; Research; VOSviewer

Neuromarketing As A Tool To Measure And Evaluate The Consumer Behaviour Of Guanding Teahouse's Social Media Advertisement - Zeng, Ian Mei; Lobo Marques, Joao Alexandre (Association for Computing Machinery, 2023)
This research aims to evaluate a Macau tea brand's social media advertising effectiveness with neuromarketing tools, including physiological monitoring that can measure emotional arousal. This research bridges the gap of social media marketing on Instagram for brands through the neuromarketing method. Data from 40 respondents were collected with iMotions software using neuroscientific tools. This research uses the stimuli of Guanding Teahouse, a newly established Macau tea brand, to evaluate social media advertising effectiveness. The neuroscientific tools – Galvanic Skin Response (GSR) sensors, Eye-tracking, Facial Expression Analysis (FEA) and emotion analysis are used to do the experiment. The data analysis was drawn from one representative respondent to measure the emotions and attention on the Instagram advertisements. Video 1 recorded 9 GSR peaks and Video 2 recorded 12 GSR peaks, both videos attention is ranging between 96-98 indexes. Results show that advertising videos should focus more on the products than the model. Moreover, the participant is more interested in Video 2, but the effectiveness of advertising is showing a lower focus on the brand and the tea. Future studies should consider comparing the video advertising effectiveness of Instagram stories and Instagram reels to prevent disruption of video on the stories ad.

Beyond Physical Boundaries—Organising a Virtual Exhibiton with NFTs for an International Conference - Estadieu, Gerald; Ng, S.O.K.M.; Martins de Abreu, F.; Farinha, D.F. (ARTECH 2023 - 11th International Conference on Digital and Interactive Arts, 2023)

Re-experiencing Street Signage with Augmented Reality around the City of Macau - Lio, Si Weng; Martins de Abreu, F. (11th International Conference on Digital and Interactive Arts (ARTECH2023), 2023)

Exploring EEG Signal Features for Predicting Post Cardiac Arrest Prognosis - Guilherme Cunha Santos, Antonio; Alexandre Lobo Marques, Joao; Rigo Jr., Luis; Paulo Madeiro, João (2023 Computing in Cardiology Conference, 2023)

Radial String Chimes: A Behavioural Driven Tangible Instrument Derived from Networked Music Performance Practices - Barbosa, Alvaro; Olga Ng Ka Man, Sandra; Estadieu, G (Ubimus 2023, 2023)
Research in ubiquitous networked music systems has unveiled the potential of behavioural-driven interaction interfaces as an effective model to cope with network communication delays in remote musical performances. Most of the techniques developed under these premises are based on digital music interfaces implemented on laptop computers or tablet devices, where a certain degree of gestural control comes as an added dimension. The purpose of this paper is to present an implementation of such type of interfaces in the form of a physical tangible musical instrument, contemplating multiple expressive possibilities. This is viable at the current stage of technological development thanks to leveraging 3D printing and laser cutting technologies for effective prototyping and testing of such a device. The paper seeks to demonstrate that this approach opens a wide range of possibilities for creating musical instruments with versatility and expressiveness beyond what is usually accomplished in traditional instruments. This implementation, entitled “Radial String Chimes,” is presented with its advantages, the challenges it faces, and the methods used to create it. Finally, the paper will offer suggestions for further developing such an instrument to unlock its potential.

Machine learning over the free-parameters of the Black-Scholes equation: Stock market and Option market - Arraut, Jorge Mario; Arraut, Ivan; Lei, Ka I. (LatinX in AI Workshop at ICML 2023 (Regular Deadline), 2023)
The Black-Scholes equation is famous for predicting values for the prices of Options inside the stock market scenario. However, it has the limitation of depending on the estimated value for the volatility. On the other hand, several Machine learning techniques have been employed for predicting the values of the same quantity. In this paper we analyze some fundamental properties of the Black-Scholes equation and we then propose a way to train its free-parameters, the volatility in particular. This with the purpose of using this parameter as the fundamental one to be learned by a Machine Learning system and then improve the predictions in the stock market.

Exploring the Current Landscape and Future Directions of Information Technology in Dance Education - Du, Wencai; Chen, Jiao; Xu, Simon (2023 26th ACIS International Winter Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD-Winter), 2023)
Dance education has undergone significant changes with the integration of information technology. Traditional dance pedagogy is now complemented by innovative digital software tools and applications. This work surveys the diverse applications of information technology in dance education at college or university level and the impact it has on teaching and learning processes. We discuss the integration of technology in various aspects of dance education, including skill development, choreography, performance analysis, VR/AR, online virtual learning, and collaborative learning. Additionally, the benefits and challenges associated with the use of information technology are also examined and the future research directions for research and practice in this field are proposed.
Keywords: College and University Education; Dance Education; Education; Federated learning; Humanities; Information Technology; Interactive; Surveys; Technical requirements; Training; Visualization; applications

Perceções das competências requeridas a futuros bibliotecários: um estudo internacional - Sanches, Tatiana; Chan, Emily (Atas do Congresso Nacional de Bibliotecários, Arquivistas e Documentalistas, 2023)
Resumo Os bibliotecários são profissionais que se devem manter constantemente atualizados, procurando ativamente o desenvolvimento das suas competências profissionais, pelas próprias características das funções que desempenham. Porém, é importante perceber o que pensam estes atores acerca da sua atual formação de base, concretamente se esta tem vindo a acompanhar as tendências de atualização. Assim, partindo de uma análise prévia ao conteúdo de diversos documentos orientadores, emanados de associações internacionais, no sentido de encontrar as competências preconizadas para a área de atuação, é realizado um questionário ao nível nacional e internacional a futuros profissionais, estudantes na área das ciências documentais. O principal objetivo é o de procurar entender, comparativamente, que habilidades e competências são valorizadas para o futuro desempenho profissional. O questionário foi aplicado a grupos de estudantes de ciências da documentação e informação em Portugal, Macau e República Checa, evidenciando-se as perspetivas comuns entre os inquiridos sobre as competências necessárias e aquelas que são recebidas na formação inicial, concluindo-se que existem ainda algumas assimetrias entre as necessidades da profissão e a formação recebida, na perspetiva dos futuros profissionais, independentemente do território a que pertencem.

How is Technology Accepted? Fundamental Works in User Technology Acceptance from Diffusion of Innovations to UTAUT-2 - Lampo, Alessandro (Association for Computing Machinery, 2023)
The decision to accept and use technology innovations has long been a source of debate across disciplines due to the complexity involved in predicting behavior. Recognizing that the subject is vast and fragmented, this paper examines the mainstream technology works to assist researchers to understand, conceptualize and select the most appropriate theoretical framework for their study. Starting with the pioneering effort on Diffusion of Innovations (DOI/IDT), the analysis considers the Theory of Reasoned Action (TRA), the Theory of Planned Behavior (TPB), the Technology Acceptance Model (TAM/TAM-2/TAM-3), the Value-based Acceptance Model (VAM), and the Unified Theory of Acceptance and Use of Technology (UTAUT/UTAUT-2) among the most important. A review of the key literature is vital to assessing and identifying research trends, as well as contributing to the discussion of emerging technologies such as Artificial Intelligence (AI), Augmented Reality (AR), Blockchain, Cloud Computing, Internet of Things (IoT), Mobile Apps, etc. Suggestions for future research paths are also provided.
Keywords: Acceptance and Use of Technology; Product Innovation; Technology Acceptance; Technology Adoption; Technology Innovation

Digital Renminbi: Impacts on Economic Integration of the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (Springer Nature, 2023)
The degree of economic integration in the Guangdong-Hong Kong-Macau Greater Bay Area (GBA), as reflected in the mobility of trade and capital flows, has been strengthened by free trade agreements, but obstacles including border effects, capital controls, differences of exchange rate systems and inadequate cross-regional coordination remain. Digital renminbi (e-CNY) has been tested in Shenzhen, a core GBA city since April 2020. If e-CNY is adopted in the GBA, the area will effectively become a single currency zone. Whether the GBA constitutes an “optimum currency area” (OCA) depends on its degree of economic integration. This paper computes real interest rate differential (RID), uncovered interest rate differential (UID) and deviation from purchasing power parity (PPD) of each regional pair based on data of interest rates, exchange rates and price indexes from 2016M2 to 2022M7. All UID, PPD and RID series have means within about 1 percent point from 0, indicating high degrees of financial integration, real integration and economic integration. With the exception of Guangdong-Macau RID, all series are stationary, implying mean-reverting behavior. Hence, the parities are expected to hold both in the short run and in the long run, which is a condition for an OCA in the GBA. Furthermore, the regression analysis finds that the test launch of e-CNY in Shenzhen (adjusted for the COVID-19 outbreak) has significant impacts on all RIDs, Guangdong-Macau PPD and Hong Kong-Macau PPD. With merely two and a half years of test launch, the introduction of e-CNY already had impacts on overall economic integration in the GBA.
Keywords: Economic development policy; Economic integration; Exchange rate regime; Financial integration; Greater Bay Area; Optimum currency area

Empirical Studies on the Conditions of Achieving Interactive Mindfulness Through Virtual Reality Single User Experience in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (Springer Nature, 2023)
Virtual reality, a computer-generated 3D environment, allows one to navigate and possibly interact, resulting in real-time simulation of one or more of the user’s five senses (Gutierrez et al., 2008; Vince, 2004). Virtual tours and places have swiftly become popular in education, professional training, arts, exhibitions, and medication and rehabilitation. The empirical studies derived from the PhD thesis research aim to identify the conditions for Macao’s single-user experience to achieve mindfulness in virtual reality through immersion and interactivity.
Keywords: Single user experience; immersion; interactivity; mindfulness; virtual reality

Training Strategies for Covid-19 Severity Classification - Pordeus, Daniel; Ribeiro, Pedro; Zacarias, Laíla; de Oliveira, Adriel; Marques, João Alexandre Lobo; Rodrigues, Pedro Miguel; Leite, Camila; Neto, Manoel Alves; Peixoto, Arnaldo Aires; do Vale Madeiro, João Paulo (Springer Nature Switzerland, 2023)
The COVID-19 pandemic has posed a significant public health challenge on a global scale. It is imperative that we continue to undertake research in order to identify early markers of disease progression, enhance patient care through prompt diagnosis, identification of high-risk patients, early prevention, and efficient allocation of medical resources. In this particular study, we obtained 100 5-min electrocardiograms (ECGs) from 50 COVID-19 volunteers in two different positions, namely upright and supine, who were categorized as either moderately or critically ill. We used classification algorithms to analyze heart rate variability (HRV) metrics derived from the ECGs of the volunteers with the goal of predicting the severity of illness. Our study choose a configuration pro SVC that achieved 76% of accuracy, and 0.84 on F1 Score in predicting the severity of Covid-19 based on HRV metrics.
Keywords: COVID-19; Electrocardiogram (ECG); Heart Rate Variability (HRV); disease severity classification; signal processing

Sustainable Practices in Hotel Chains—A Comparative Analysis of Official Annual Hospitality Sustainable Reports from Listed Companies in Macau SAR, China - Santos, Ana Sofia Kong; Marques, João Alexandre Lobo (Springer International Publishing, 2023)
In the last few years, the tourism industry has experienced rapid expansion and diversification, making it one of the fastest-growing financial industries in the world. Consequently, the hotel industry has significantly affected the environment's long-term viability. Many hotels have begun voluntarily implementing environmentally sustainable practices as they become more aware of their ecological footprint. There has been a great deal of discussion about the effects of hotel operations on the environment and tourism sustainability in Macau. It is because of these negative impacts that hoteliers have adopted green practices in an attempt to minimize them. By developing sustainability reports, hotels can set goals, measure performance, and manage change, resulting in better sustainability. It could also be viewed as a strategy to enhance the company’s sustainability reporting to ensure stakeholders know what the company does. The objective of this study is twofold based on the analysis of the official sustainability reports of four major hotel chains. Firstly, seven categories of sustainable practices effectively adopted by these chain hotels are identified and clusterized. Second, it is presented in which areas some hotels performed more efficiently than others, considering the UN Sustainable Development Goals (SDGs) as a reference. The results allow a comprehensive clusterized analysis of the industry in a highly developed gaming and entertainment area of South China and create a clear comparison between relevant players and their concerns about sustainability practices.
Keywords: Environmentally sustainable practices; Macau hotels; Sustainable development goals (SDGs); Sustainable reports; Tourism industry

Consumers' Adoption of Molecular Chinese Medicine (MCM) in Macau: A Value-based approach - Hong, Chi Kit; Lampo, Alessandro (Academy of Global Business Research and Practice, 2022)
Molecular Chinese Medicine (MCM) is a recent method of manufacturing and dosing prescriptions that brings several advantages when compared with Traditional Chinese Medicine (TCM). For instance, MCM is highly dissoluble, tastes better than the usual decoction, and the active principles are easily absorbed. Also, the manufacturing process is subject to better quality control. In spite of these benefits, consumers' intentions remain unclear due to the novelty of this technique. Therefore, an assessment of individuals' perceptions is relevant since molecular medicine is redefining how scientists understand and treat diseases, and it can be considered a medical innovation. To fill the research gap, the Value-based Acceptance Model (VAM) (Kim et al., 2007) is used to assess the individuals' perceptions of value and intention to accept MCM. Data from a sample of Macau residents are analyzed by means of structural equation modeling (SmartPLS). The results support the use of the model in our context, thus extending the applicability of the VAM to other settings. Except for 'technicality', the constructs of 'usefulness', 'enjoyment', and 'perceived fee' had a significant impact on the overall 'perceived value' of MCM, and in turn on the behavioral intention to use the innovation. To facilitate the diffusion of this dosage method in the marketplace, it is suggested that communications strategies consider the proposed sources of value when promoting MCM. To further explain the adoption process, it is recommended to include additional factors that may affect consumers' intention to adopt the innovation and extend the analysis to the actual usage.

A Model of Integrating Bert and BiGRU+ Attention Dual-channel Mechanism for Investor Sentiment Analysis of Stock Price Forecast - Ma, Huawei; Ma, Jixin; Liang, Shengbin; Du, Wencai (2022 IEEE/ACIS 23rd International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2022)

A Model of Integrating Bert and BiGRU+ Attention Dual-channel Mechanism for Investor Sentiment Analysis of Stock Price Forecast - Ma, Huawei; Ma, Jixin; Liang, Shengbin; Du, Wencai (2022 IEEE/ACIS 23rd International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2022)
Investor sentiment and emotions have a strong impact on financial markets. In recent years there has been increasing interest in analyzing the sentiment of investors for stock price prediction using machine learning. Existing prediction models mostly depend on the analysis of trading data and company profit. few prediction theories have been built based on individual investors' sentiments. The fundamental reason is the difficulty to measure individual investors' sentiment.

Investigation on citizen trust towards e-government services in GBA – A study on WeChat and Alipay government service mini-programs - Lai, Chimeng; Joao, Alexandre Lobo Marques (Association for Computing Machinery, 2022)
Citizens' trust in eGovernment is crucial for the successful implementation of new electronic services. This relationship in the Greater Bay Area (GBA) plays an essential role since the Government services rely on mobile mini-programs This study investigates the trust towards government service mini-programs in WeChat and Alipay. A user feedback questionnaire was designed, and a total of 609 valid samples were collected from Shenzhen, Guangzhou, Hong Kong, and Macau. The findings imply that competence, integrity, and benevolence are the key components of trust in e-government (TIEG). TIEG positively influences perceived value (PV), which positively affects citizens' Intention to adopt service mini-programs. PV significantly mediates the relationship between TIEG and Intention. Although TIEG does not effectively reduce perceived risk (PR), risk issues cannot be ignored in the adoption process. Finally, this article proposes relevant implications and suggestions for the GBA government agents and policy makers.

How Social Influence and Image Impact on the Intention to Use a Technology: A Study from the Battery Electric Vehicle Domain - Lampo, Alessandro; Silva, Susana C. (Association for Computing Machinery, 2022)
Technology research offers several theories and models to explain how individuals accept and use technology innovations. While these often focus on the technical aspects of the innovation, they tend to downplay the affective component of technology. Recognizing that the adoption of technology is also determined by what it means and represents to the users, this paper aims to fill the gap in the literature by studying the effects of social influence and image on the behavioral intention to adopt a technology. We used structural equation modeling (SmartPLS) to analyze data collected from 238 self-administrated surveys regarding the behavioral intention of Macau residents to use battery electric vehicles. The result showed significant relationships among the variables in the model and depicted the construct of image as a strong factor in the adoption decision. Our findings suggest that social influence may not exhibit substantial impact in the case of innovations in their initial phase and, more importantly, the construct of image could be included as a key predictor of behavioral intention in technology acceptance models, particularly in contexts where the choices that consumers make are public, and therefore subject to judgments from the members of the community.
Keywords: Battery Electric Vehicles; Image; SmartPLS; Social Influence; Technology Acceptance

Economic Integration in the GBA: a Price-Based Assessment of Real and Financial Integration in the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (Association for Computing Machinery, 2022)
The Guangdong-Hong Kong-Macau Greater Bay Area (GBA) was first conceptualized in 2016, which aimed to facilitate trade and finance liberalization among the three regions. The trade and financial environment of the GBA is unique. Due to the “one country, two systems” principle, Mainland China, Hong Kong and Macau are considered to be trading partners bounded by WTO rule, but bilateral free trade agreements have been signed between Mainland China and Hong Kong, and between Mainland China and Macau, but not between Hong Kong and Macau. Furthermore, each of the three regions circulates a local currency subject to its own exchange rate policy, with Hong Kong Dollar and Macau Pataca currently pegged to the US Dollar. These affect the mobility of trade and capital flows in the area. Hence, this paper applies the widely-used price-based approach due to Cheung et al. [5] to analyze the degrees of real and financial integration in the GBA based on interest rates, exchange rates, and price indexes data from January, 2016 to November, 2021. The real interest differential (RID), uncovered interest differential (UID) and the deviation from purchasing power parity (PPD) between each regional pair have means that are statistically and economically close to zero, implying high real and financial integration in the GBA. The unit root tests for stationarity also confirm that the time series are mean-reverting, so the economic integration in the GBA in the long run is foreseeable.
Keywords: Economic development policy; Economic integration; Financial Integration; Greater Bay Area

The future of Cosmetics Advertisement Strategy: A Neuromarketing Study using Electrodermal Activity (EDA) as a measure of Emotional Arousal - Neto, Andreia; Lobo Marques, Joao Alexandre (Association for Computing Machinery, 2022)
Neuromarketing lies at the intersection of three main disciplines: psychology, neuroscience, and marketing, and it has been a successful neuroscientific approach for the study of real-life choices such as consumer behavior [1]. A current gap in the cosmetics field is the lack of published research studies, considering the marketing investment done yearly in this category. With the rapid economic expansion and the rise of social media in China, consumers' interest in beauty is growing. Even though the Chinese cosmetics sector is rapidly expanding, no studies have been done with Chinese consumers. This study aims to employ the same approach as previously done in consumer neuroscience studies to evaluate cosmetic brands' marketing strategy to understand better if immediate emotional responses can be measured using Electrodermal Activity (EDA). Here, we focus on cosmetics products advertisement as a model to understand consumer preference formation and choice. Eighteen Chinese female consumers were recruited between 19 and 37 years old. From the results obtained, it was understood that none of the participants have voted for the product advertisement for which they showed higher emotional arousal. However, it appears that the participants' preference is for the products for which the brand awareness is stronger since the product advertisements with more votes are the ones for the Korean brand used. The product advertisements with Asian faces were the ones with more votes, suggesting that Asian faces have engaged consumer preference. However, the product advertisements for the Brazilian brands, unknown to the Chinese public, were the ones with fewer votes, although, those product advertisements were the ones with more emotional arousal per minute. Those advertisements were also those with non-Asian faces, suggesting that this feature influenced voting decisions. From this study, it has been observed that Electrodermal Activity is a measure of emotional arousal that by itself cannot be translated into consumer engagement. Therefore, it is also proposed to evaluate brand awareness in future studies related to product advertisements. The physical features of the people included in the advertisements is also suggested to be further evaluated in future studies since a different cultural background seems to influence the consumers' engagement. Furthermore, using EDA to complement other neurophysiological tools like facial expression analysis is also suggested for future studies to have evidence about the nature of the emotions raised.
Keywords: advertisement; consumer behavior; consumer neurosciences; cosmetics; marketing; neuromarketing

Entrepreneurial Process of SMEs in Macau - Phillips, Jenny O. L.; Oliveira, Nelio (Association for Computing Machinery, 2022)
In recent years, entrepreneurship and innovation have been highly propagandised for Macau's economic development, diversification, and the Greater Bay Area (GBA). Since 2013, efforts have been exerted by the Macau government to encourage and support entrepreneurship, from the launching of the Young Entrepreneurs' Aid Scheme in 2013 and the Macau Young Entrepreneur Incubation Centre in 2015. While the failure rate of startups has been considered high in most parts of the world, the rate was only as low as 14% in Macau, with many businesses created every year. This research aims to study the unique entrepreneurial environment for small-to-medium enterprises (SMEs) starting up in Macau from the experience of local entrepreneurs who are benefactors of government support. In-depth interviews were conducted to understand the experience and perceptions of these entrepreneurs as they go through each stage of the entrepreneurial process. Existing research on entrepreneurial processes varies from the two-stage process, which focuses on the beginning of an enterprise, to the different models of various stages from ideas generation to exit or long-term development. From the consolidation of the literature on the entrepreneurial process, five key stages were taken to guide this qualitative research. Findings suggested that idea validation at the start of the entrepreneurial process is almost non-existent amongst our research subjects. Yet it does not affect the implementation and growth of these SMEs. The growth strategies tend to be steady and for the long term, with most SMEs having no consideration of an exit plan.
Keywords: Economic diversification; Entrepreneurial process; Government entrepreneurship aids

The Application of Nudge Theory in Ensuring Change Acceptance in the Hospitality-Gaming Industry – A Case Analysis from Macau SAR, China - Tagulao, Thea Clarice Saavedra; Marques, Joao Alexandre Lobo (Association for Computing Machinery, 2022)
As the rate of change increases exponentially, organizations must adapt quickly to the business landscape's volatility, uncertainty, complexity, and ambiguity (VUCA). As a result, organizations must implement agile strategies and practices to ensure their responsiveness and readiness to any changes brought about by internal or external factors. With a greater number of changes, change agents are tasked with implementing various change management methodologies to ensure that change recipients accept change initiatives. This research will look at one of the methodologies used by change agents, the use of nudges from Thaler and Sunstein's Nudge Theory, which is a subtle intervention to influence an individual's decision-making with the goal of steering them towards a specific desired outcome; and analyze their effectiveness towards the change recipients when implemented. Change agents were interviewed on the application of Nudge Theory to change recipients when managing to change initiatives within their respective organizations. The results indicate that the use of nudges created by the change agents can significantly impact the level of resistance from the change recipients. If used correctly, the Nudge Theory can mitigate change resistance, and the success of a change initiative is higher. But, if change recipients are forced to comply, their resistance will be greater, affecting the organization overall.
Keywords: Change Initiatives; Change Resistance; Nudge Theory; Organizational Behavior; Organizational Change Management

Intersectoral Linkages in Booming Sector Economies - Gomes, Sérgio Ricardo Santos; Marques, Joao Alexandre Lobo; Reis, Ricardo Ferreira (ICEME 2022: 2022 13th International Conference on E-business, Management and Economics, 2022)

Experience the Past in the Present with Immersive Technologies - Chang, Tin Lan; Martins de Abreu, F. (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
Countless historical sites worldwide have become unrecognisable based on their historical context. Many are cultural heritage structures with significant historical and aesthetic importance. The majority have not been well preserved; worse, some were demolished (Stenning, 2015). Furthermore, structures are part of a dynamic and changing environment, and their location within the original landscape is not always clear. People have gradually forgotten cultural traditions as environments where historical stories took place, and the look and feel have been corrupted. Immersive Virtual Reality (V.R.) allows us to relive and explore the past. However, in the Pearl River Delta Region, specifically Macau S.A.R., V.R. is still in its infancy and is not frequently used for reproducing historical sceneries. Our research focuses on reproducing heritage structures and scenery based on scarce historical information. It shows how to incorporate facts and memories into the design and create engaging, immersive experiences in V.R. scenery that takes place, both inside and outside of a cultural heritage site that has lost its original appearance. Following this, a prototype was created with specific parameters relating to past and present sceneries. We partially reproduced an existing building complex currently being used for creative and commercial purposes, but it was a shelter for the poor and a house for old ladies to live in. There were not enough facts or images linked to the inner space in the past. Inadequate information allows audiovisual scene creators to be more imaginative. The prototype focuses on a functional design that integrates cultural traits tied to local industries. The researcher used image processing software, and web 3D tools (A-Frame 1.1.0). Users can navigate by virtually “walking” and starting the visual tour; simultaneously, the story unfolds as the timeline progresses. After entering, the users jump from the present to a specific era in the past. With audio guidance, users enter the private space, shared areas, working space, etc. Users can interact with objects from the virtual scenes while the interface displays relevant audiovisual introductions. Users could utilise the virtual system to learn how the old ladies led their daily lives in the Pearl River Delta Region and grasp the local single ladies’ group lifestyle at a specific time in the past (Kwong, 2020). The interactive experience enhances the users’ interest; additionally, the users become more familiar with the region’s traditional customs. With this approach, we can create old stories using modern technology. A-Frame provides users with great convenience and can be used by any Internet browser without relying on professional V.R. devices. The content from this usage provides a greater understanding of our heritage buildings and their historical context to the wider community. This could be used in other heritage sites worldwide to reproduce and maintain structural qualities over time. This immersive experience could be a means to navigate the past while in the present. This application could benefit exhibition developers, and visitors, notably in exhibition guided tours, virtual tours inside museums, or educational assisted historical storytelling.

Macao Soundscape as an Analysis Tool for Sound Quality Assessment - Pestana, Pedro; Barbosa, Alvaro; Estadieu, Gerald (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
Macao SAR, China is one of the more densely-populated territories in the world, and as such necessarily struggles with Soundscape quality. Nonetheless, the territory has already been identified as a unique location for to function as a Soundscape living lab (Cordeiro et al., 2014), since it has a very small manageable area that includes many types of geographical varieties, from extremely high density urban areas to natural environments with dense vegetation highland or varied water front typologies. In addition, Macao has extremely wide multicultural population with a broad range of subjects that have diverse cultural perceptions and thresholds in regards to sonic cognition. The potential impact of this diversity has already been noticed in both tourism (To & Chung, 2019) and research (Chung et al., 2016). The concept of Soundscape itself is garnering increased awareness as a viable alternative to assess the quality of the sonic environment, of use to policy management and legislation, shown not only by the increasing numbers of scientific articles on the subject (Moscoso et al., 2018), but also by recent international standardisation efforts in measuring it (ISO,2018). In this talk we shall give a preliminary description and illustration of the Soundscape in a territory that is rich in diversity and has huge potential for citizen participation. This includes approaches like noise mapping, sound mapping, Soundwalks, grounded theory efforts for detailed descriptions of the environment and use of alternative objective metrics. We will describe how to use the richness of this gathered data in developing artificial-intelligence algorithms to autonomously assess and predict the evaluation of a given Soundscape based on recordings alone. This goal will alleviate the intense human effort in subjective assessment, and may prove to be an effective and substantial diagnostics tool in planning the soundscape for prospective built environments, functioning not only as an analysis and diagnostics tool, but as a design strategy for a sustainable sonic future.

International Student Diversity Experiences in their Host Cities - Ge, Yun; Ho, Kong Chong (Governing Diverse Cities in Europe and AsiaAt: Singapore, 2022)

INNOVATING IN OPEN DISTANCE TEACHING WITH FACE-TO-FACE RETREATS WITHIN A DOCTORAL PROGRAM IN DIGITAL MEDIA ART - Fernandes-Marcos, A; Tavares, M (IATED Academy, 2022)

Study of the Compositional Rules of Design in Chaoshan Traditional House: A Computational Approach - Afonso, Filipe (Association for Computing Machinery, 2022)
This study is an attempt to understand and describe the compositional principles of Chaoshan traditional houses (CTH) through a computational space syntax. In this approach, the space syntax is used to describe and verify the compositional rules of Chaoshan houses. Chaoshan rural residence is a classical Lingnan style building in Chaoshan area of eastern Guangdong province, associated with Teo-Swa people, a Han Chinese minority. This study takes the example the prototypes existing in the village of Zhupu, Haojiang District, Shantou city as a case study, to analyse the spatial form of the residences. The Zhupu village houses date from the Qing Dynasty - Qianlong period, around 1700 AD. The hypothesis of this study is that CTH buildings are a result of a space compositional rule system that can be described and replicated through a computational design methodology. This study will establish a computational architectural syntax, and is the first stage of an extended research work on the evolution of Chaoshan residential types. The understanding of this evolution may help, as future work, to develop urban strategies for adaptation of the CTH heritage buildings to the contemporary living conditions. As the result of this study is a computational 3D graphics modelling algorithm, the ability of the system to generate the house layouts is not limited to the reconstruction of existing typologies of CTH and its variations. The same algorithm will allow the generation of new housing schemes, with adaptation to design variables extracted from a particular site and region.
Keywords: Chaoshan house; Qing dynasty; Space syntax; computational design; courtyard house

Book of Proceedings of ARTeFACTo2022MACAO, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities. 24-25 Nov. 2022, Macao. IEEE ISBN 979-8-3503-1004-7 - Estadieu, Gerald (2022 Third International Conference on Digital Creation in Arts, Media and Technology (ARTeFACTo), 2022)

Understanding Stakeholders’ Perspectives Towards Serious Games for Vocational Training for People with Intellectual Disabilities in Macau - Lei, Choi On; Cardoso, Jorge C. S. (Springer International Publishing, 2022)
People with intellectual disabilities need vocational training and support in order to be able to get into the work market and maintain their workplace. In Macau SAR, China, the vocational training ecosystem still operates in fully classic, in-person, fashion, which means it is susceptible to pandemic situations such as COVID-19. This causes a big disruption to the training when isolation measures are in place. Our goal is to study the introduction of serious games for vocational training of people with disabilities in Macau. This work presents a study to assess the training benefits of serious games and usability factors, understand the acceptability and adoption factors/benefits of serious games for vocational training for people with intellectual disabilities and associated stakeholders in Macau.
Keywords: People with intellectual disabilities; Serious games; Vocational training

Applied Interactive Mindfulness: a virtual reality grave mourning user experience in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
It has been proven in numerous research that mindfulness can be helpful to reduce stress and chronic pain (Hall, 2014; Lindström, n.d.; Tong et al., 2015). While interactive mindfulness has been one of the focuses in the recent mobile applications market, usually tackling three essential human senses: audio, visual, and touch, each mobile application has quite some different approaches in terms of interactivity. Some focus on the touch and visual, and some on audio (environmental sounds or instructing meditation). Immersing oneself in virtual reality (VR) creates a constant stream of interactivity. Nonetheless, what are the conditions for an (in)tangible virtual reality to be more effective? Under the COVID-19 pandemic and lockdown since the end of 2019, Macao has been facing a social concern that we cannot travel easily to visit our decedents’ graves abroad, let alone the existing concerns of expensive burial services, lack of space, and alternative burial options. Also, taking into consideration that standard funeral service in Macao is often too brief, and getting briefer, thus lacking the opportunity to properly farewell the decedent, this research is proposing a virtual reality 3D model construction of the Chapel of St. Michael, located in St. Michael the Archangel Cemetery in Macao, to be streamed on a 360 virtual tour platform, Kuula. co. By immersing in this virtual reality, the participant is to have a single user experience for mindfulness with the decedent. To ensure valid and reliable results that address the research aims and objectives, a single-user experiment is going to be set up with multiple electronic devices, namely, the smartphone iPhone X with cardboard VR, the tablet iPad Pro, and the Oculus Quest 2. The methodology to collect the data will be using observation and simulation. The experiment will be started with an introduction to the project and conducted with no instruction, allowing users to explore and examine all features in this immersive experience. Along with a post-experience survey (interview + questionnaire), we seek its conditions and impacts on Macao residents in terms of interactive mindfulness and participants’ expectation of testing, for the first time in Macao, a virtual reality grave mourning experience.

(Un)Directed Reading, an interactive kiosk to encourage writing and reading - Olga Ng Ka Man, Sandra; Estadieu, Gerald; Farinha, Daniel (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
(Un)Directed Reading is an interactive installation (Edmonds, 2010) initially derived from the “Directed Reading” course, which all undergraduate students at the University must take during their final year. In this course, students are assigned different writing exercises and research assignments to open their creative and constructive minds in writing (EdwardsGroves, 2012; McVey, 2008). Every year, at the end of the course and after a selection process, a collection of stories is uploaded to a database of original stories. We then developed an open-source application to print a receipt ticket from a thermal printer with a randomly picked story every time a user pushes a button. An arcade game-style button is installed on a kiosk designed in collaboration with students and set on the university's campus (left photo). The printed receipt presents a short extract of one of the stories and a QR code that links to the full story decorated with illustrations. In a modern society where most of our interactions are audiovisual-based, young generations are less and less encouraged to read and even less to write. By offering a simple kiosk installation with short stories and graphical illustrations, we propose a new interactive interface that can easily engage passers-by to eventually stimulate their reading and creativity. By reading these stories, students, professors, staff, and visitors can be surprised by the talent of our students, as it stimulates students to write new pieces to be selected. The interactive kiosk was accessible to all for a period of 3 months with 23 stories during which we automatically collected some data to use in quantitative analysis. In this first run, we focused on data from the user's interactions such as story printed, story read, date and time. It allowed us to see the ratio between the printed receipt and the actual online reading of a story and more.

Replacement or plume fallout? Both, please! Evidence from active and fossil VMS systems - Relvas, J M R S; Barriga, F; Pinto, A; Marques, A F; Carvalho, J; Dias, A Á (16th SGA Biennial Meeting 2022, 2022)

Nowcasting Gross Domestic Product and Gross Gaming Revenue of Macau: a Theoretical and Conceptual Framework - Chau, Manuel; Lei, Weng Chi (The 5th Academia-Industry Exchange Institute of International Business & Governance (IIBG) Symposium 2021, 2021)
This paper aimed to build up the theorical and conceptual understanding of future forecasting study of Macau’s GDP and Gross Gaming Revenue (GGR) by co-movement of economic indicators. Macau GDP and GGR showed co-movements with a number of time series economic indicators, including China’s exports and imports, China’s manufacturing PMI, non-manufacturing PMI, China's electricity production growth, share price of some Macau’s gaming operators, etc. These time series data can be found in statistics departments of China, Macau and Hong Kong, stock exchanges, and international organizations such as the International Monetary Fund (IMF), the World Bank, the World Trade Organization (WTO). Burns and Mitchell’s study in 1946 identified co-movements between economic indicators and being further carried out and developed leading, coincident and lagging indicators, which is essential for future econometric models and nowcasting techniques developments to study these co-movements. In particular, with the proper application of nowcasting techniques, future studies can exploit the data of leading and coincident economic indicators to forecast Macau’s GDP and GGR within an acceptable level of error. Since Macau is a “monotown,” where the gaming revenue makes a significant contribution to the economy. The forecasting of gaming revenue is crucial as it aids the gambling and tourism industries in preparing supply and provides information to policymakers to plan for the near future. This research also contributes to understand Macau’s economy by investigating its internal and external economic variables.

Orbital Eccentricity. Sound performance, using commercial and military satellites with real time tracking data - Paquete, Hugo; Bernardino Bastos, Paulo; Fernandes-Marcos, Adérito (ARTECH 2021: 10th International Conference on Digital and Interactive Arts, 2021)
Keywords: Micro Sound; Performance; Sonification; Sound art

Inside the embroidery. The rematerialization of traditional embroidery in a post-digital approach: No interior do bordado. A rematerialização do bordado numa vertente pós-digital - Pereira, Selma; Fernandes-Marcos, Adérito (ARTECH 2021: 10th International Conference on Digital and Interactive Arts, 2021)

Contemporary art as a factor for knowledge generation from video: A arte contemporânea como fator de geração de conhecimento a partir do vídeo - Urrutia, Hernando; Pérez, Pilar; Fernandes-Marcos, Adérito (ARTECH 2021: 10th International Conference on Digital and Interactive Arts, 2021)

A Comprehensive Review of Investor Sentiment Analysis in Stock Price Forecasting - Ma, Huawen; Ma, Jixin; Wang, Han; Li, Pengsheng; Du, Wencai (2021 IEEE/ACIS 20th International Fall Conference on Computer and Information Science (ICIS Fall), 2021)
Sentiment analysis technologies have a strong impact on financial markets. In recent years there has been increasing interest in analyzing the sentiment of investors. The objective of this paper is to evaluate the current state of the art and synthesize the published literature related to the financial sentiment analysis, especially in investor sentiment for prediction of stock price. Starting from this overview the paper provides answers to the questions about how and to what extent research on investor sentiment analysis and stock price trend forecasting in the financial markets has developed and which tools are used for these purposes remains largely unexplored. This paper represents the comprehensive literature-based study on the fields of the investors sentiment analytics and machine learning applied to analyzing the sentiment of investors and its influencing stock market and predicting stock price.
Keywords: Analytical models; Information science; Investor sentiment analysis; Machine learning; Market research; Predictive models; Reliability; Sentiment analysis; Social media; Stock price trend forecasting; Tools

A Machine Learning Approach to Predict the Trend of Obesity Prevalence at a Global Level - Barzinji, Ala Othman; Ma, Chaoying; Du, Wencai; Ma, Jixin (2021 IEEE/ACIS 6th International Conference on Big Data, Cloud Computing, and Data Science (BCD), 2021)

A Prospective analysis about employee retention strategies for Macao Hotel Industry - Chong, Ka Yee; Lobo Marques, Joao A. (Association for Computing Machinery, 2021)
Human resources are essential to the survival, success, and long-term growth of a company. Hotel is an industry requiring a high level of human resources for delivering high-quality personal service to the hotel guests to maintain its competitiveness in the business environment. With the rapid economic growth in Macao started in 2002, all the industries have been growing fast and competing fiercely for the limited manpower in Macao. However, the Macao hotel industry has been losing its attractiveness in the Macao labor market and needs to rely on non-local workers with a limited stay in Macao. The management team of the Macao hotel industry is looking for a solution to maintain a stable workforce. Therefore, a study has been conducted on the effectiveness of its employee retention strategies. A questionnaire was designed to collect the preferences of the employees and interviews were conducted to understand the perspective of the management team toward the employee retention strategies. The study shows the employee strategies are focused on key employees’ interests such as career development and prospect. However, the communication between the management team and employees failed and led to employee turnover.
Keywords: Employee retention; Employee turnover reasons; Macao hotel industry; Macao shortage of manpower

Sustainable Buildings’ Projects – A Perspective from Consultants and Contractors based in Macau SAR, China - J.P.P. Santos, Eduardo; Lobo Marques, Joao; Phyllips, Jenny O. L. (Association for Computing Machinery, 2021)
China growing awareness of sustainability has brought out relevant aspects to move towards a green environment. Since its subscription in 2016, China has been committed to implementing the Paris Agreement, and the Greater Bay Area (GBA) development plan prioritizes ecology and pursuing green development. The primary purpose of this research is to perceive the companies' insights concerning the implementation of sustainable buildings’ projects in Macau. For this multi-case study analysis, primary data was gathered from interviews with two groups involved in the construction projects’ lifecycle: Consultants and Contractors, to analyze different perceptions and concerns. The interviews considered two different themes about the main topic: (1) Perception on Companies’ Experience in Sustainable Projects; (2) Key Drivers towards Sustainable Buildings’ Projects’ Implementation. In conclusion, according to the analyzed data, it is essential to notice that companies’ background and the market particularities affect their corporate performance specially connected to the green construction frameworks. The data also indicate that it is necessary to move towards regulations and policies to change corporate and people's mindset.
Keywords: Construction industry; Green building; Sustainable Policies; Sustainable building

The Influence of Society on the Behavioral Intention to Use a Technology: Evidence from the Battery Electric Vehicles Domain - Lampo, Alessandro; Silva, Susana C. (European Marketing Academy, 2021)
Despite the general good intentions towards the environment, individuals tend to adopt traditional internal combustion vehicles. Drawing from technology research, this study focuses on the impact of society - in the form of subjective norm and image – on the behavioral intention to adopt a technology. More precisely, this study seeks to explore to which extent societal influences drive the behavioral intention to adopt battery electric vehicles (BEV) technology. A self-administered survey was used for this purpose. The analysis of the data from a sample of 111 respondents showed significant relationships between the predictors and the target behavioral outcome. The study also revealed that subjective norm and image are particularly significant factors for the segment of BEV owners. The findings suggest that marketers and practitioners incorporate social elements into their product communication strategies in order to encourage the uptake of environmentally-sound technologies.

COVID-19: Short-Run Impacts of the Pandemic on the Integrated Resort Oligopoly of Macao - Lei, Weng Chi (The International Workshop Tourism and Hospitality Management (IWTHM2021), 2021)
Objective: As a world tourist destination, Macao is inevitably under the impact of the COVID-19 pandemic. However, the market of integrated resorts in Macao are shared by only a few casino concessionaries, together forming an oligopoly. While the firms attempted to adjust price, quantity and quality of their hotel services in response to the pandemic, they could not overlook the strategic interactions with other players in the market. Hence, this paper aims to investigate the possible impact of the pandemic on the oligopolistic strategies in the integrated resort market in Macao. Methodology: Application of a theoretical model of differentiated oligopoly to this six-firm case shows that price differences across firms depend on their quality differentiation. In order to analyze these price differences empirically, this paper collects data of hotel room rates of the integrated resorts from November, 2019 to mid-August, 2020, covering the periods before and after the outbreak of COVID-19. Originality: In the existing literature, there is a lack of studies of the oligopoly in the hospitality industry of Macao. Furthermore, the effect of COVID-19 is still ongoing, so this present paper is one of the first to perform such analysis. Results: The regression of each of the hotel price differentials on the COVID-19 dummy variable shows that COVID-19 has statistically significant impacts on almost all the price differentials. Intuitively, MGM and Wynn were in the high-price segment before and after the outbreak, while other firms switched positions in the low-price segment during the pandemic. One obvious downstream movement was by Conrad. According to the proposition derived from the theory, these imply that COVID-19 should have significant impact on the quality differentiation of the firms. Practical implications: The results are in line with the observations that the integrated resorts have rolled out staycation packages according to preferences of local residents. These quality adjustments observed in Macao’s hospitality industry currently only involved variable inputs rather than fixed inputs of production; therefore, the impact of COVID-19 should be seen as short-term effects. Keywords: Covid-19; Differentiated oligopoly; Hospitality industry; Hotel room rate; Oligopolistic market structure; Pricing strategy.

Students’ wellbeing during the Covid-19 pandemic - Ikegami, Kiiko (The International Webinar of University Riau Conference, 2021)

Research on Quality Control of Intelligent Injection Molding System Based on Process Monitoring - Han, Wang; Shasha, Lv; Shaobin, Li; Wencai, Du; Qinggu, Li; Bo, Wang (2021 8th International Conference on Computational Science/Intelligence and Applied Informatics (CSII), 2021)

Statistical Methods to Forecast Air Quality in Taipa Ambient and Taipa Residential of Macao - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (Springer, 2021)
Air pollution is a major concern issue on Macao since the concentration levels of several of the most common pollutants are frequently above the internationally recommended values. The low air quality episodes impacts on human health paired with highly populated urban areas are important motivations to develop forecast methodologies in order to anticipate pollution episodes, allowing establishing warnings to the local community to take precautionary measures and avoid outdoor activities during this period. Using statistical methods (multiple linear regression (MLR) and classification and regression tree (CART) analysis) we were able to develop forecasting models for the main pollutants (NO2, PM2.5, and O3) enabling us to know the next day concentrations with a good skill, translated by high coefficients of determination (0.82–0.90) on a 95% confidence level. The model development was based on six years of historical data, 2013 to 2018, consisting of surface and upper-air meteorological observations and surface air quality observations. The year of 2019 was used for model validation. From an initially large group of meteorological and air quality variables only a few were identified as significant dependent variables in the model. The selected meteorological variables included geopotential height, relative humidity and air temperature at different altitude levels and atmospheric stability characterization parameters. The air quality predictors used included recent past hourly levels of mean concentrations for NO2 and PM2.5 and maximum concentrations for O3. The application of the obtained models provides the expected daily mean concentrations for NO2 and PM2.5 and maximum hourly concentrations O3 for the next day in Taipa Ambient air quality monitoring stations. The described methodology is now operational, in Macao, since 2020.

Quality Detection Method for Controller Process Based on Mask R-CNN Network Model - Ma, Xinlei; Chen, Yanyu; Li, Shaobin; Du, Wencai; Tan, Zehan; Li, Qinggu; Ma, Yaqi; Deng, Haiyan (2021 8th International Conference on Computational Science/Intelligence and Applied Informatics (CSII), 2021)

The concept of “Object-image” revisited through the interactive-film installation “Sense of Place” - Caires, C. S; Estadieu, G (Besides the Screen 2020, 2020)

Oxyhydroxide Hydrothermal Crusts from Saldanha Hydrothermal Field - Costa, Pedro; Dias, Ágata (Goldschmidt2020, 2020)

Sub-Seafloor Sulfide Mineralization in the Saldanha Hydrothermal Field, Mid-Atlantic Ridge (MAR) - Dias, Ágata; Qiu, Wenhong; Barriga, Fernando J A S; Tao, Chunhui (Goldschmidt2020, 2020)

Ore-Forming Process of the Menez Gwen Hydrothermal Field: In situ S Isotopes and Trace Metals Constraints - Dias, Ágata; Qiu, Wenhong; Costa, Isabel Maria Amaral; Barriga, Fernando J A S (Goldschmidt2020, 2020)

Mangroves as ecosystem services providers in an urban context: case study of Macao, SAR China - Vanessa, W. L.; Calheiros, Cristina S. C.; Tagulao, Karen (4th Meeting – online edition – Functional Biology and Biotechnology of Plants, 2020)

Mangroves as nature-based solution for coastal water eutrophication in Macao, SAR China - Vanessa, W. L.; Calheiros, Cristina S. C.; Tagulao, Karen (CIIMAR, 2020)

Joseph Ma Xiangbo – the John Henry Newman of China? An Attempt to Rehabilitate an Underdog “Father” of Chinese Catholicism 若瑟馬相伯 – 中國的若望享利紐曼? 試替一位無名的中華公教教父振聲 - Law, Cyril Jerome (Macau Ricci Institute Forum, 2019)

Potential for the design of an energy saving facade system using agglomerated cork: Implications in subtropical climates - Afonso, Filipe (The 2nd International Conference on Sustainable Buildings and Structures, 2019)

Hydrothermal Fe-Mn deposits from low-temperature systems of the Mid-Atlantic Ridge - Costa, P; Dias, Ágata (InterRidge Workshop on Hydrothermal Ore-forming Processes, 2019)

Diving into the unknown: robotics as tools to study the deep-sea. Informed Scientific Sampling in Large-scale Outdoor Environments - Dias, Ágata (International Conference on Intelligent Robots and Systems IROS, 2019)

Geochemistry of Fe-Si-(Mn) Chimneys from Luso Vent Field, MAR - Dias, Ágata; Costa, P; Marques, A F; Ribeiro, L; Madureira, P; Calado, A; Gonçalves, E; Morato, T (Goldschmidt, 2019)

Sulfide mineralization of the Saldanha hydrothermal field (MAR): constraints from sulfur isotope in-situ microanalysis - Dias, Ágata; Qiu, W; Barriga, F; Tao, C (InterRidge Workshop on Hydrothermal Ore-forming Processes, 2019)

Geochronological, geochemical and petrographic constraints on incremental pluton growth: the case of Macao granitic suite - Dias, Ágata; Quelhas, P; Mata, J; Wayne, Davis (Goldschmidt, 2019)

Microsoft Power BI Desktop for Data Analytics - NEGREIROS, J. Garrott Marques; MARQUES, JA Lobo (2019)

Fast Cluster-learning with Prior Probability from Big Dataset - Li, Tengyue; Fong, Simon; Lobo Marques, Joao Alexandre; Wong, Raymond K. (2018 5th International Conference on Soft Computing & Machine Intelligence (ISCMI), 2018)
Association Rule Mining by Aprior method has been one of the popular data mining techniques for decades, where knowledge in the form of item-association rules is harvested from a dataset. The quality of item-association rules nevertheless depends on the concentration of frequent items from the input dataset. When the dataset becomes large, the items are scattered far apart. It is known from previous literature that clustering helps produce some data groups which are concentrated with frequent items. Among all the data clusters generated by a clustering algorithm, there must be one or more clusters which contain suitable and frequent items. In turn, the association rules that are mined from such clusters would be assured of better qualities in terms of high confidence than those mined from the whole dataset. However, it is not known in advance which cluster is the suitable one until all the clusters are tried by association rule mining. It is time consuming if they were to be tested by brute-force. In this paper, a statistical property called prior probability is investigated with respect to selecting the best out of many clusters by a clustering algorithm as a pre-processing step before association rule mining. Experiment results indicate that there is correlation between prior probability of the best cluster and the relatively high quality of association rules generated from that cluster. The results are significant as it is possible to know which cluster should be best used for association rule mining instead of testing them all out exhaustively.
Keywords: Association Rule Mining; Big Data; Clustering; Clustering algorithms; Data mining; Itemsets; Preprocessing; Prior Probability; Probabilistic logic; Probability distribution

A origem e evolução dos magmas graníticos de Macao à luz de dados de geoquímica elementar e isotópica / Source and evolution of Macao granitic magmas: insights from wholerock geochemistry and isotopic signatures. - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Ribeiro, M L; Borges, R (XIV Congresso de Geoquímica dos Países de Língua Portuguesa e XIX Semana de Geoquímica (XIV CGPLP/XIX SG, international conference, 2018)

Hacking: Toward a Creative Methodology for Cultural Institutions - Estadieu, G; Caires, C. S (2018)

Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (ARTECH2017: Eighth International Conference on Digital Arts, 2017)

Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Association for Computing Machinery, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

Sounding Architecture: Inter-Disciplinary Studio at HKU - Barbosa, Alvaro; Tsang, Thomas (Aalborg University, 2017)
Sounding Architecture, is the first collaborative teaching development between Department of Architecture and Department of Music at the University of Hong Kong (HKU), introduced in Fall 2016. In this paper we present critical observations about the studio after a final public presentation of all projects. The Review was conducted with demonstrations by groups of students supervised by different Lecturer, in each case focusing on a different strategy to create a connection between Sound, Music, Acoustics, Space and Architectural Design. There was an assumption that the core working process would have to include the design of a new musical instrument, which in some cases became the final deliverable of the Studio and in other cases a step in a process that leads to a different outcome (such as an architectural Design, a performance or social experiment). One other relevant aspect was that Digital technology was used in the design and fabrication of the physical instruments' prototypes, but in very few cases, it was used in the actual generation or enhancement of sound, with the instruments relying almost exclusively in acoustic and mechanical sound.

Variation in students' conceptions of classroom management - Correia, Ana (International Symposium on Education and Psychology (ISEP), 2017)

Using digital reading platforms to develop Chinese elementary students' English reading - Correia, Ana; Norte, Patrícia; Garrot, João (International Symposium on Education and Psychology (ISEP), 2017)

New geochemical constraints on I-type granites of Macao: evidences for fractional crystallization and petrogenetic affinities with Jurassic-Cretaceous granites in SE China - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Borges, R; Ribeiro, M. L (Goldschmidt, 2017)

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (ACM, 2017)

Computer Literacy Teaching Using Peer Learning and Under the Confucian Heritage Cultural Settings of Macao, China - Wong, Kelvin; Neves, Ana; Negreiros, João (2017)
University students in Macao are required to attend computer literacy courses to raise their basic skills levels and knowledge as part of their literacy foundation. Still, teachers frequently complain about the weak IT skills of many students, suggesting that most of them may not be benefiting sufficiently from their computer literacy courses. This research proposes an enhanced framework based on constructivist principles by using peer-tutoring to increase cost effectiveness and to improve student outcomes. Essential to this proposed model is the training of former course graduates as peer-instructors to achieve high quality learning results. At Instituto de Formação Turistica (IFT), a case study was used to evaluate its effectiveness using a qualitative analysis. In Macao, most students have a Confucian Heritage Cultural (CHC) background and the current findings demonstrate that students share more easily their learning difficulties within their group as their interpersonal relationships improve. It is suggested that since CHC cooperative learning is primarily based on bonds, students involved in this 'relationship-first, learning-second' type shared a larger amount of knowledge and social skills, a dual positive outcome. Moreover, English language is a major barrier for the understanding of the teacher’s message to Chinese students. Meanwhile, the negative Western concept of plagiarism is replaced, under the CHC, as the ‘face giving’ and it is directly based on the relationship intensity to 'help friends'. At last, peer-tutors play a key role in the student increase internal motivation regarding the joy of the learning process.

Petrology and Geochemistry of Granitic Rocks from Macao - Dias, Ágata; Quelhas, P; Lou, U; Mata, J; Ribeiro, M L (Goldschmidt, 2016)

Employees’ Dissonance in non-gaming industries A Casino Dominant Econom - Kuok, A.C.H. (2016 Global Conference of Education and Psychology, 2016)

Assessing Driving Behavior in Public Transportation through Mobile Crowd Sensing: A Concept Proposal for Macau Public Transportation System - Ma, Fa Chun; Tóng, Sok Hán; Cordeiro, João (2016 10th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS), 2016)
This paper introduces a concept proposal for accessing driving behavior in public transportation through Mobile Crowd Sensing (MCS), as part of a long-term research project on Advanced Public Transportation System (APTS). The proposed concept makes use of mobile device's accelerometer and passengers' qualitative evaluation to identify aggressive driving behavior, which is believed to be a major factor for unnecessary accidents and fuel consumption. A survey and comparison of IT services (mobile applications and websites) provided by Macau Government and private bus companies in Macau, regarding bus-related information, such as fares, routes and route diversions is also provided.

Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices A case study with Macao-chinese girls - Correia, Ana; Fernandes, Clara; Maia, Joao (Third International Conference on Advances In Economics, Social Science and Human Behaviour Study - ESSHBS 2015, 2015)
This study explores girls’ attitudes and selfassessment of abilities towards mathematics and science and its effects on career preferences. Results from Pi

Globalization, Communication, Information and Cohabitation - Simoes, José Manuel (8th Annual Conference of the Chinese Association of Global Communication, 2015)

Environmental Urban Design and Planning Rules and their Impact on Street Spaces in Hong Kong and Macau - Tieben, Hendrik; Chu, Joanna; Soares, Nuno; Yiu, Edward (8th Conference of the International Forum on Urbanism (IFoU), 2015)

Saldanha hydrothermal field: the role of the sediment-cover in the preservation of ore-forming minerals - Dias, Ágata; Barriga, F (Third InterRidge Theoretical Institute: Magmatic and Tectonic Processes and Seabed Resources at Mid-Ocean Ridges. T2-09, 2015)

Are the devotions of the Passion of Jesus in Macao still a "Dangerous memory"? - Eleutério, João Marques (Asian Conference on Ethics, Religion & Philosophy, 2015)
Among the multiple images used to promote Macao as a touristic destination, we can find some related with the Christian traditions, in particular with the Catholic devotions to the Passion of Christ and the cult of the Virgin Mary. Discussing the concept of “dangerous memory” as proposed by Johann Baptist Metz and analyzing the rituals associated with the devotions around the Passion of Jesus, this paper aims to look at, and present, the different perceptions of a message of subversion of unbalanced relations of power and domination, such as the image of the suffering Jesus in the contemporary society of Macau. The method followed in this paper is ethnographic and structured around some major contributions in the field of Ritual Studies. The implications of this research are related with the different perceptions and usages of a religious image and the drift of its power.

Contemplation on Today’s Digital Education - Negreiros, João; de Fatima Oliveira, Maria (Springer International Publishing, 2015)
This paper starts to address the affect and side-effects of social media on people’s live in a pure contemplation perspective. Social networks are revised and some issues regarding its impact on education was not forgotten such as the teacher role in the digital classroom, formal versus informal learning or Web 2.0 tools use. Since Moodle is the first Learning Management System whilst Facebook is the first social network in the world, a survey was accomplished with two independent classes of e-business students at University of Saint Joseph, Macao, China, on their attitudes toward both online services in a learning framework. In general, the results confirms to a certain extent others previous studies on the question of whether using Facebook as an educational tool is more effective than Moodle.
Keywords: Education; Facebook; Macao; Moodle; Social Networks

Cross-Adaptive Polarity Switching Strategies for Optimization of Audio Mixes - Pestana, Pedro; Reiss, Josh; Barbosa, Alvaro (2015)

Engaging School Students with Tangible Devices: Pilot Project with .NET Gadgeteer - Thota, Neena; Estadieu, Gerald; Ferrao, Antonio; Meng, Wong Kai (2015 International Conference on Learning and Teaching in Computing and Engineering (LaTiCE), 2015)

MOOCs and their impact on academics - Sheard, Judy; Eckerdal, Anna; Kinnunen, Päivi; Malmi, Lauri; Nylén, Aletta; Thota, Neena (Association for Computing Machinery, 2014)
Massive Open Online Courses (MOOCs) have recently become a hot topic in the academic world, launching a wide ranging discussion on a number of issues. In this research, we surveyed academics' awareness, attitudes, perceptions, and experiences of MOOCs. We received responses from 236 academics from 23 countries, who were working in different roles such as teachers, researchers, managers, and pedagogical developers. Participants were invited to answer questions concerning their awareness and attitudes towards MOOCs. For participants with some knowledge of MOOCs, we requested their experiences and their observations of the impact of MOOCS on their students, teaching colleagues, and within their institutions. We found the most common reaction to MOOCs amongst the academics was concern but many were positive about the phenomenon. The academics claimed their students could be motivated to take MOOCs because of flexibility and no cost involved. While many academics were not aware of their students taking a MOOC and had not observed any changes to teaching programs at their institutions because of MOOCs, there was evidence of some activity and future plans for engagement in MOOCs.
Keywords: MOOCs; academics; distance learning; e-learning; massive open online courses; open learning; pedagogy

Teaching and learning with MOOCs: computing academics' perspectives and engagement - Eckerdal, Anna; Kinnunen, Päivi; Thota, Neena; Nylén, Aletta; Sheard, Judy; Malmi, Lauri (Association for Computing Machinery, 2014)
During the past two years, Massive Open Online Courses (MOOCs) have created wide interest in the academic world raising both enthusiasm for new opportunities for universities and many concerns for the future of university education. The discussion has mainly appeared in non-scientific forums, such as magazine articles, columns and blogs, making it difficult to judge wider opinions within academia. To collect more rigorous data we surveyed teachers, researchers, and academic managers on their opinions and experiences of MOOCs. In this paper, we present our analysis of responses from the computer science academic community (n=137). Their feelings about MOOCs are highly mixed. Content analysis of open-ended questions revealed that the most often mentioned positive aspects included affordances of MOOCs, freedom of time and location for studying, and the possibility to experience teaching from top-level international teachers/experts. The most common negative aspects included concerns about pedagogical designs of MOOCs, assessment practices, and lack of interaction with the teacher. About half the respondents claimed they had not changed their teaching as a result of MOOCs, a small number used MOOCs as learning resources and very few were engaging with MOOCs in any significant way.
Keywords: computing academics; distance learning; e-learning; moocs massive open online courses; open learning; pedagogy

A Glimpse into the Cultural Situatedness of Computer Science: Some Insights from a Pilot Study - Berglund, Anders; Thota, Neena (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
To what extent is students' understanding of computer science culturally situated? This, possibly philosophical question, has come to the surface at Uppsala University, Uppsala, Sweden, where many Chinese students study computer science together with the local students. We did an exploratory study using email interviews to see if our intuitions could be relied on. We collected data from Chinese students studying in master programs and analysed the data using a phenomenographic perspective. A complex intertwined relationship between the content of their learning (the WHAT), the ways in which they went about studying (the HOW), the aims of their studies (the WHY), and the competencies developed from the intercultural context they studied in (the WHERE) was observed. In this paper we offer some insights from the results of the pilot study and discuss how they have shaped our on-going study in the field.
Keywords: Computer science; Context; Cultural differences; Educational institutions; Global communication; Interviews; computer science education; cultural context

Programming Course Design: Phenomenographic Approach to Learning and Teaching - Thota, Neena (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
Phenomenography is a well-known empirical research approach that is often used to investigate students' ways of learning programming. Phenomenographic pedagogy is an instructional approach to plan learning and teaching activities. This theoretical paper gives an overview of prior research in phenomenographic studies of programming and shows how the results from these research studies can be applied to course design. Pedagogic principles grounded in the phenomenographic perspective on teaching and learning are then presented that consider how to tie students' experiences to the course goals (relevance structure) and how to apply variation theory to focus on the desired critical aspects of learning. Building on this, an introductory object-oriented programming course is described as an example of research-based course design. The insights gained from the experience of running the course are shared with the community of computer science educators, as also the benefits and responsibilities for those who wish to adopt the phenomenographic perspective on learning to plan their teaching. The development of an increased awareness of the variation in students' ways of experiencing programming and the need to broaden the context of the programming course are discussed.
Keywords: Communities; Computer languages; Education; Programming profession; Syntactics; Writing; introductory programming; object-oriented programming; phenomenography; variation theory

Images of Law in Chinese Crime Fiction - Morais, Isabel (2014)
Crime fiction in China emerged in the 1890s in translations of Western works, and evolved from the mere imitation of Western crime fiction to becoming an autonomous literary genre. Despite fluctuations in popularity, the genre of Chinese crime fiction, the plots of which are based on true cases, has retained a reasonably constant presence on the literary scene, and has captured the popular imagination in contemporary China and, more recently, across the world. After the demise of Mao, under whose governance the genre was banned, the government of the early Deng regime began to favor so-called “legal system literature” (fazhi wenxue), and aimed to use it to propagate moral principles and maintain political control in opposition to writers who strived for independence and originality. Since the mid and late 1980s, which were considered the heyday of Chinese crime fiction, and the expansion of the legal system and legal institutions, crime fiction has served to illuminate the role of law and to display new social perceptions. To investigate these attitudes, I focus on works of contemporary Chinese crime fiction by arguing that they are expressions of a confluence of cultural exchange and new trends. Several factors may have contributed to such a change, from the impact of the cinema and television serials in China to the celebrity status of Chinese detectives, lawyers and judges both as crime solvers and writers in the Chinese mainland and amongst the Chinese writing diaspora. An important finding is that besides giving detailed descriptions of legal procedures, all of the works studied have clearly shifted away from the traditional formula of Chinese crime fiction, that is, of the quest of a hero for justice, punishment, and revenge, to focus on the process of solving crime and the rendering of justice through legal processes. It seems that crime fiction is becoming crucial in conveying a new understanding of citizen’s rights in an attempt to fit into ongoing contemporary debates on universalistic notions of justice and the competence of legal institutions to provide justice to increasingly marginalized sectors of contemporary China.

Using smartphones as personal monitoring tools for the acoustic environment - Cordeiro, Joao; Barbosa, Alvaro (2014)

The Foundation of Soundscape-Lab in Macau. - Cordeiro, Joao; Barbosa, Alvaro; Martins, Luis; Gomes, Jose (2014)

Promoting Awareness for the Acoustic Phenomenon: a Survey of Pedagogical Practices and Research Projects Developed at EA/CITAR - Cordeiro, João; Gomes, José Alberto; Gonçalves, Miguel (Invisible Places, 2014)
At EA/CITAR (School of Arts/Research Centre in Science and Technology of the Arts), sound has always assumed a fundamental role, both in academic research and curricular offer, featuring a Master Program in Sound Design and a Doctoral Program Specialization in Computer Music. This paper presents an overview of some recent artistic/research projects undertaken by students and researchers at this institution, which stimulate the user/listener awareness for the acoustic phenomenon. Furthermore, we describe three pedagogical practices, stemming from Soundscape and Film Sound studies, which aim at training students to avoid the devious influence of sight on the assessment of soundscapes.

The fiction of Fernanda Dias and Senna Fernandes: Revisiting colonial Macau through the lens of ethnicity, gender and patriarchy - Correia, Ana; Borges, Vera (Proceedings of The European Conference on Cultural Studies 2014, 2014)

Sr and Nd isotopic composition of Jan Mayen and Loki’s Castle: a progress report - Cruz, M I; Marques, F A M; Dias, Ágata; Pedersen, R; Barriga, F (43rd Underwater Mining Institute, 2014)

Composing with Soundscapes: an Approach Based on Raw Data Reinterpretation. - Gomes, Jose; Pinho, N.; Lopes, F.; Costa, G.; Dias, R.; Barbosa, Alvaro (2014)

Attitude and perception towards green products in Macao: An exploratory study - Lampo, Alessandro; Leong, Sin U (13th Society for Global Business & Economic Development (SGBED 2014), 2014)

Engaging: Creative Placemaking in Macau and Hong Kong - Mendes, Carla de Utra; Simões, José Manuel (Individual, Community & Society: Conflict, Resolution & Synergy, 2014)
Nowadays, contemporary art practices have been expanding into fields outside their own borders. According to Claire Bishop (2012), this expanded field of post-studio practices currently goes under a variety of names: socially engaged art, community-based art, experimental communities, dialogic art, littoral art, interventionist art, participatory art, collaborative art, contextual art and (most recently) social practice. By engaging, artists nurture the sense of belonging and search for an identity of the place they inhabit. In Hong Kong and Macao, as well as in the Pearl River Delta and China in general, the speed of urban transformation is forcing artists to reconsider their participation in the city in order to develop a creative place making process that is according to the new identity of the place. By doing so, they are also included in what has been defined as “creative industries” that tries to build a new image of the urban fabric. Linked with this sort of collective attitude, there is also an attempt to find a sense of local identity that has been disappearing in the face of these major developments. Engaging with the city and the communities may constitute, therefore, a challenge for the young generation, especially in hybrid places such as Hong Kong and Macao, where artists find themselves in an effort to understand the core values of their fragmented identity. In this paper we will analyze some projects that artists are doing in both SAR´s, in order to create a sense of place in this state of transition.

Endogenous fragmented technology and optimal offshoring in large civil aircraft production - Lei, Weng Chi (The 9th Annual Conference of the Asia-Pacific Economic Association, 2013)
This paper is motivated by two observations in the large civil aircraft (LCA) industry. (1) Boeing and Airbus are significantly different in the degree of offshoring. (2) The degree of offshoring also changes among different aircraft models. To offer an explanation, this paper focuses on issues related to fragmentation. Existing literature has established the tie between fragmented technology and offshoring. However, it is assumed that production can be fragmented readily and at no cost; and only exogenous global economic factors have impact on the degree of fragmentation. This model distinguishes itself from others by incorporating endogeneity in fragmentation. A final-good firm can spend on R&D specifically for its own fragmented technology. As a result, the final-good firm can optimally choose the portion of components to be offshored. A strategic trade policy model is used to show that the degree of offshoring depends on the firm's own cost of production, the host country's cost of production, the global state of technology as well as the government trade policies. In particular, export subsidy and subsidy on R&D of fragmented technology are shown to be policy substitutes. Keywords: Fragmentation; Offshoring; Outsourcing; Aircraft; Export subsidy; R&D subsidy; Boeing; Airbus JEL classification: F12; F13; F23; L13

Computer Science Students' Perception of Computer Network Security - Cambazoglu, Volkan; Thota, Neena (2013 Learning and Teaching in Computing and Engineering, 2013)
In the last decade, the progress of internet technologies has led to a significant increase in security and privacy issues for users. This study aims to investigate how computer science students perceive computer network security. Thirty three students participated in the study in which we gathered data through a questionnaire. In this paper, we present an analysis that is inspired by the phenomenographic approach. Our conclusion is that the students have different levels of understanding of computer network security depending on their usage of the concepts they have learned, their theoretical or practical orientation to the subject, and their interest in the field.
Keywords: Computer Network Security; Computer Science Education Research; Computer security; Educational institutions; Protocols; Training; Wireless networks

Facebook as an Informal Learning Space Channel: The São José, Macao Cases - Kio, Su Long; Negreiros, Joao (2013 Learning and Teaching in Computing and Engineering, 2013)
Broadly, on-line communication platforms are online resources that allow the exchange of information using the Internet. They include Email, Instant Messaging, Online Open Forums, Online Blogging and Social Networking Sites. All these platforms have their own specialties and properties. In education, there are great advantages for high-schools to utilize these online communication platforms, especially Online Open Forums and Social Networking Sites. Communication is the backbone of education. Everything from classroom teaching to school policy making depends on effective communication [1]. With these new communication platforms at hand, schools can develop more adaptable and friendly channels among students, teachers and management (only the first two interveners are covered under this study). Various components of the schools will essentially work together in a more collaborative and regenerative way [2]. This research paper analyses how online communication platforms are changing the internal nature of education. It takes sample populations from two schools in Macao (Pre-University of the University of Saint Joseph, USJ, and Colégio Diocesano de São José, CDSJ) with different backgrounds such as medium of language, level of degree, professor's background and style of teaching. Teachers of these schools are communicated first for their opinion on key elements to improve learning with online communication platforms. These factors are implemented in a platform such as Social Networking Sites. As expected, students are instructed to utilize this platform (Facebook) to enhance their learning practice and experience. The result of this utilization is assessed in terms of student opinions and feedback.
Keywords: Educational institutions; Electronic mail; Facebook; Internet; Macao; Visualization; communication; incidental education; social networking sites

Monitoring Temporal Personal Information Regarding Soundscapes and Movement, as a Way to Enhance Social Interactions - Barbosa, Alvaro; Cordeiro, Joao (Springer - Lecture Notes in Computer Science, 2013)

NIME Education at the School of Arts of the Portuguese Catholic University / CITAR - Barbosa, Alvaro; Martins, Luis (2013)

Loudness Measurement of Multitrack Audio Content Using Modifications of ITU-R BS.1770 - Barbosa, Alvaro; Pestana, Pedro; Reiss, Josh (2013)

Soundscape-Sensing in Social Networks. - Cordeiro, Joao; Barbosa, Alvaro (2013)

A Soundscape Assessment Tool Based On A Massive Multichannel Loudspeaker Setup - Cordeiro, Joao; Barbosa, Alvaro; Santos, A. (2013)

Prospects and pitfalls of being a good communicator: Contemplating the career choices of female students in Macau - Correia, Ana; Marques, Tania (8th Annual Conference of the Asian Studies Association of Hong Kong, 2013)

Sulphide mineralization in Arctic seafloor hydrothermal fields: extending the European exploration area to the Far North - Cruz, M I; Dias, Ágata; Pedersen, R B; Relvas, J M R S; Fonseca, R; Barriga, F J A S (ERA-MIN., 2013)

Sulfide Sites in the Arctic Ocean: Jan Mayen and Loki’s Castle, Mineralogical Magazine - Cruz, M I; Marques, A F; Dias, Ágata; Pedersen, R; Relvas, J M R S; Barriga, F J A S (Goldschmidt, 2013)

Are Luminous Devices Helping Musicians to Produce Better Aural Results, or Just Helping Audiences Not To Get Bored - Joaquim-Fernandes, Vitor; Barbosa, Alvaro (2013)

Spectral Characteristics of Popular Commercial Recordings 1950-2010 - Pestana, Pedro; Reiss, Josh; Ma, Z.; Barbosa, Alvaro (2013)

Computer science at school/CS teacher education: Koli working-group report on CS at school - Schulte, Carsten; Hornung, Malte; Sentance, Sue; Dagiene, Valentina; Jevsikova, Tatjana; Thota, Neena; Eckerdal, Anna; Peters, Anne-Kathrin (Association for Computing Machinery, 2012)
In an international study, experts reflected on their national state of computer science education in school, and the associated situation and education of computer science teachers. While these situations are shaped by local circumstances, they are also shaped by changes in the discipline. The results of the study showed a number of recurrent themes and patterns such as curriculum difficulties, training and support for teachers, as well as the understanding (e.g. computer science vs. information technology) and relevance of computer science. The study also draws attention to initiatives that are being undertaken at the local and international levels to solve these problems. Finally, the study points out trends which are -- according to the experts asked -- likely to occur within the next few years.
Keywords: CS at school; CS ed research; CS teacher education; curriculum; goals; international comparison; pedagogy; study; topics

Critical development of green marketing in the hotel industry: Macao case study - Lampo, Alessandro; Gregori, Gian Luca; Cardinali, Silvio; Temperini, Valerio (SGBED Research Symposiums：Doing Well by Doing Good: New Perspectives on Corporate Social Responsibility, Sustainability, and Inclusive Capitalism, 2012)
This study analyzes the green marketing strategies with specific reference to the hotel industry. The concept of green marketing in this sector is crucial due to the growing expected importance of tourism in the future of global economy and its potential impact on social and economic development; this is true particularly in areas with relevant volumes of tourist arrivals. In this sense, we carried out an exploratory research in the hotel industry of the Special Administrative Region (SAR) of Macao in order to: highlight the primary motivations that underlie interventions geared towards the eco-sustainability of hotels, the services they offer and point out the problems, issues, and future prospects in the development of green marketing, as well as explore the role of eco-sustainable values in hotels’ online communication policies. In order to reach these aims a qualitative research was carried out with a semi-structured questionnaire (face-to-face interviews) to a group of hotels. The research was finished by an analysis of their websites, in order to verify possible references to the steps taken to protect the environment.

Shaped by use. Urban space appropriation in Macau - Soares, Nuno (PNUM 2012 - Portuguese Network of Urban Morphology, 2012)
The contemporary city is a complex system where a multitude of factors and dwellers interact, creating a multi-layered spatial structure that supports the urban life. To successfully research and intervene in this context, one needs to develop fitting approaches and methods to be able to analyze it in depth.

Perfect Take: Experience Design and New Interfaces for Musical Expression - Barbosa, Alvaro; Makelberge, Nicolas; Perrota, Andre; Ferreira, Luis Sarmento (NIME, 2012)

Accuracy of ITU-R BS.1770 Algorithm in Evaluating Multi-track Material - Barbosa, Alvaro; Pestana, Pedro; Reiss, Josh (Audio Engineerg Soceity, 2012)

The gender gap in science, engineering, technology & mathematics: unfolding traditional mindsets - Correia, Ana; Marques, Ana (Proceedings of Fifth International Conference of Education, Research and Innovation, 2012)

Illustration of paradigm pluralism in computing education research - Thota, Neena; Berglund, Anders; Clear, Tony (14th Australasian Computing Education Conference, ACE 2012, 2012)
This paper argues for paradigm pluralism in computing education research. The value of mixing paradigms, and the choice of methodological eclecticism and mixed methods is explored using pragmatic knowledge claims. A research study, which focused on the design of an introductory object-oriented programming (OOP) course for undergraduate students, is introduced as an illustration of paradigm pluralism. The study demonstrates methodological eclecticism and use of mixed methods for data collection and analysis. Meaningful outcomes resulting from the choice of the research design are described. A framework that focuses on the research problem and research questions to guide research design is presented as the outcome of the study. Through the discussion and demonstration of paradigm pluralism, this paper contributes to increased awareness of theoretically anchored research in computer science. © 2012, Australian Computer Society, Inc.

Repertory grid: investigating personal constructs of novice programmers - Thota, Neena (Association for Computing Machinery, 2011)
In this paper, the repertory grid is presented as a technique to explore novice programmers' experiences within the context of an action research project. The theoretical and methodological aspects of the technique are discussed. The findings from the technique that combined quantitative and qualitative data analysis methods are provided. These findings relate to the learning process, learning content, and learning support as experienced by the students in an introductory object-oriented programming course. The repertory grid technique is then appraised for its relevance and usefulness to the project, and for its contribution to the diversity of computer science research methods. Insights gained from the use of the technique are shared with the community of computer science educators.
Keywords: mixed methods; novice programming; repertory grid

Macao: A Study on the Impact of Global, Regional and Local Forces. - Lampo, Alessandro; Care, Leanda (Signapore Management University, 2011)
Over the years Macao has been exposed to different cultures and has been influenced by various political and economic interests. The booming casino economy has ultimately transformed the city into the largest gambling hub in the world. In spite of the consensus about Macao's shiny future, there are factors (such as the large reliance on a single industry) and socio-economic problems (such as labor shortage, unequal income distribution, and inflationary pressure) that moderate the optimism. By making use of the Chatterjee and Nankervis' convergent and divergent process model for management, this paper examines how global, regional, and local forces have impacted the economic development process, form and type of organizations in Macao. The paper also suggests that the government implement a framework that develops and diversifies the economy but also takes into consideration the social needs of the community.

Evaluating an Enterprise Content Management for the Macao Government Agency - Pong, F.; Whitfield, R.; Negreiros, J. (Springer, 2011)
Information contained within documents is an essential ingredient of any office operation. A content management application (CMA) is an organization plan for the conception, use, retention, disposal and selective preservation of its data. Using an appropriate CMA framework can greatly help Macao Government agencies, for instance, that are increasingly using electronic means to create, exchange and store a major variety of records daily. By definition, a record is information, in whatever form, for government functions, activities, decisions and other important transactions. As expected, as the volume of electronic information increases, so does the complexity of managing electronic records. This project goal was to evaluate the software capabilities of the Alfresco© Enterprise Content Management (ECM) against a set of functional requirements, aimed by the Macao Government agency. Drawing on the results of this evaluation, the present analysis concludes that Alfresco© ECM is capable of supporting an entire agency needs related to the management of its records content.
Keywords: Alfresco©; Enterprise Content Management; Macao Government; Open Source Software

Preservation and Sustainability of Industrial Heritage in the Urban Renewal: A Case Study of Iec Long Firecracker Factory in Taipa, Macao - Zhu, Rong; Pinheiro, Francisco Vizeu (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
As an incomparable implication of industrial culture, the industrial heritage has a wide range of historical, technological, social, architectural or scientific values. With the process of large-scale contemporary urban revitalization, abandoned industrial buildings and areas always become the targets of urban renewal and redevelopment due to the ongoing transformation on structural changes of economy and adjustments of plot usage. Although the research and discussion on preservation of industrial heritage have been launched in the fields of theory and practice in China, many former industrial areas and buildings are still undergoing extreme threats and irreversible damages. Taking Iec Long Fireworks Factory which is the only well preserved survivor of industrial heritage in Macao as a case study, this paper presents its historic background, present challenges and future envisions of development. Based on group investigations and SWOT analysis, integrated strategies are proposed to preserve and revitalize the old factory ruins and their landscape settings. The conclusions show the significance to preserve and reuse industrial heritage opened for the urban renewal, which also could be a good contribution for sustainability of history and culture, environment, society and tourism.
Keywords: Architecture; Buildings; Cultural differences; Fires; History; International Committee; Production facilities

Towards the Creation of a New Sustainable Urban Environment: Improvement and Revitalization of Public Spaces in the Historical Centre of Macao - Zhu, Rong; Pinheiro, Francisco Vizeu (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
Contemporary urban environment is facing big changes caused by a series of synthetic factors on politics, economy, technology, society and culture. Its goals and design concepts have shifted from the fulfillment of the basic function of life into the improvement of whole qualities of cities. Forming the key part of city fabric, urban historical centre helps link scattered individual historical buildings, and retrieve urban fabric. It also takes important roles in preserving history and tradition, keeping social meanings of a place and city's sustainability. This paper briefly analyzed the historic background and current issues in Macao Historic Centre. Meanwhile, strategies and principles are proposed to improve and revitalize public spaces located in dilapidated or misused historical centre so as to provide new scientific and holistic ideas for the creation of a new sustainable environment in China.
Keywords: Asia; Cities and towns; Fabrics; Green products; History; Publishing; Urban areas

Achieving acceptable air quality in Macao through sustainable transportation - Ezeka, Franklin A.N; Chan, Sek Kiu (International symposium on the progrees of technology in environmental impact assessment, 2010 Macao international environmental co-operation forum & exhibition, 2010)

Crticial analysis of the policy and implementation of the environmental protection education of Macao - Chan, Sek Kiu; Li, Siu Pang, Titus; Ma, William (Partnerships beyond boundaries: new horizons in environmental education, 2009)

As subculturas organizacionais e a avaliação de escolas: genealogia de uma relação conflitiva em estudo de caso - Correia, Ana; Costa, Jorge (Proceedings of II Simpósio sobre Organização e Gestão escolar, 2002)

Geochemical and mineralogical investigations of seafloor oxyhydroxides deposits collected in Mid-Atlantic Ridge hydrothermal fields - Costa, P; Dias, Ágata (Goldschmidt 2020)

Variability of the hydrothermal fields within the Portuguese seafloor (MAR) - Dias, Ágata; Relvas, J.M.S.Relvas; Marques, A. F.; Qiu, Wenhong; Barriga, F J A S; Ribeiro, L; Calado, A (Goldschmidt 2022)

The evolution of sulfur isotope in hydrothermal fluids along the formation of chimney of Menez Gwen (MAR): mineralization implications - Qiu, W; Dias, Ágata; Costa, Isabel Maria Amaral; Barriga, F (Goldschmidt 2022)